The Financial System of the Medieval Papacy in the Light of Recent Literature - Lund, W. E. (Quarterly Journal of Economics, 1909)
I. Literature. Character previous to the opening of the Vatican Archives, 251. — Notable recent works, 254. — II. Administration. Development of a financial department, 260. — Central organization, 263. — External agents, 267. — III. Revenues. Classification, 273. — Census, 275. — Income taxes, 280. — Benefice taxes, 282. — Fees and miscellaneous receipts, 292.